LEGAL REVIEW OF THE IMPLEMENTATION OF CERTIFICATION OF ENDOWMENT LAND TO AVOID DISPUTES FROM A POSITIVE LEGAL PERSPECTIVE IN INDONESIA BASED ON THE VALUE OF LEGAL CERTAINTY - Herman , Herman; Henry Aspan; Mhd. Azhali Siregar (PT. Sinergi Legal Publisher, 2025)
Certification of waqf land plays an important role in ensuring legal certainty and preventing disputes that often occur due to unclear ownership status. In Indonesian positive law, waqf land is regulated in Law Number 41 of 2004 concerning Waqf and Government Regulation Number 42 of 2006, which requires every waqf land to be registered and certified by the National Land Agency (BPN). However, in practice, many waqf lands have not been certified due to lack of public awareness, administrative limitations, and bureaucratic obstacles. As a result, waqf land often becomes the object of dispute, especially when the heirs of the waqif try to reclaim the assets that have been donated. This study analyzes the implementation of waqf land certification to avoid disputes in a positive legal perspective based on legal certainty. Using the normative juridical method, this study examines the laws and regulations and obstacles in the implementation of waqf land certification in Indonesia. The results of the study indicate that waqf land certification can provide legal protection for waqf assets and ensure that the land continues to be utilized in accordance with the established social and religious objectives. Therefore, it is necessary to increase the effectiveness of certification through digitalization of land services, simplification of administrative procedures, and increasing the role of Nadzir in managing waqf land. With a better certification system, legal certainty for waqf land can be guaranteed, thereby avoiding potential disputes and strengthening the role of waqf in the social and economic development of the community.